2010
DOI: 10.1155/2010/697583
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Vallecular Cysts as a Cause of Dysphagia: Case Report and Literature Review

Abstract: Cysts of the vallecula are rare, accounting for 10.5% to 20.1% of all laryngeal cysts. Vallecular cysts may present with diverse symptoms affecting the voice, airway, and swallowing. We describe the evaluation and treatment of a 70-year-old woman who presented with dysphagia caused by large bilateral vallecular cysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 9 publications
0
31
0
4
Order By: Relevance
“…1 Of the laryngeal cyst, vallecular cysts accounts for 10.5% to 20.1% of all laryngeal cysts. 2 The most common location of epiglottic cyst is lingual surface of the epiglottis. DeSanto et al reviewed 238 cases of laryngeal cysts over a period of 10 years and found that 134 (52%) were arising from the epiglottis 3 .…”
Section: Discussionmentioning
confidence: 99%
“…1 Of the laryngeal cyst, vallecular cysts accounts for 10.5% to 20.1% of all laryngeal cysts. 2 The most common location of epiglottic cyst is lingual surface of the epiglottis. DeSanto et al reviewed 238 cases of laryngeal cysts over a period of 10 years and found that 134 (52%) were arising from the epiglottis 3 .…”
Section: Discussionmentioning
confidence: 99%
“…(7,9) The most common form of laryngeal cysts is the ductal cyst, which frequently presents at the true vocal fold, followed by the epiglottis and vallecula. (6) Clinically, there is a bimodal distribution in the age of presentation, thus suggesting two forms of vallecular cysts -adult and paediatric. (6,10) While vallecular cysts in children are rare, there is a higher prevalence in neonates and infants.…”
Section: Case Reportmentioning
confidence: 99%
“…(6) Clinically, there is a bimodal distribution in the age of presentation, thus suggesting two forms of vallecular cysts -adult and paediatric. (6,10) While vallecular cysts in children are rare, there is a higher prevalence in neonates and infants. (5,11) There are also reports of cysts detected during the antenatal period via sonography and magnetic resonance imaging.…”
Section: Case Reportmentioning
confidence: 99%
See 1 more Smart Citation
“…Cysts involving the vallecular regions are uncommon lesions and represent 10.5% to 20.1% of all laryngeal cysts [1]. Vallecular cysts (VC) are rare lesions mostly encountered in the pediatric age group and usually present within the first few weeks of life [2,3].…”
Section: Introductionmentioning
confidence: 99%